Validated Reverse-Phase High-Performance Liquid Chromatography for Quantification of Furosemide in Tablets and Nanoparticles - Ibrahima Youm; Bi-Botti Celestin Youan (Journal of Analytical Methods in Chemistry, 2013)
A simple, sensitive, and specific method for furosemide (FUR) analysis by reverse-phase-HPLC was developed using a Spherisorb C18 ODS 2 column. A chromatographic analysis was carried out using a mobile phase consisting of acetonitrile and 10 mM potassium phosphate buffer solution: 70 : 30 (v/v) at pH 3.85, at a flow rate of 1 mL·min−1. The UV-detection method was carried out at 233 nm at room temperature. Validation parameters including limit of detection (LOD), limit of quantitation (LOQ), linearity range, precision, accuracy, robustness, and specificity were investigated. Results indicated that the calibration curve was linear () in the range of 5.2 to 25,000 ng·mL−1, with ε value equal to  L·M−1·cm−1. The LOD and LOQ were found to be 5.2 and 15.8 ng·mL−1, respectively. The developed method was found to be accurate (RSD less than 2%), precise, and specific with an intraday and interday RSD range of 1.233–1.509 and 1.615 to 1.963%. The stability of native FUR has also been performed in simulated perilymph and endolymph media (with respective potency in each medium of % and %, ) after 6 hours. This method may be routinely used for the quantitative analysis of FUR from nanocarriers, USP tablets and release media related to hearing research